2021
DOI: 10.1002/ajmg.a.62113
|View full text |Cite
|
Sign up to set email alerts
|

Nager syndrome in patient lacking acrofacial dysostosis: Expanding the phenotypic spectrum of SF3B4‐related disease

Abstract: Nager syndrome epitomizes the acrofacial dysostoses, which are characterized by craniofacial and limb defects. The craniofacial defects include midfacial retrusion, downslanting palpebral fissures, prominent nasal bridge, and micrognathia. Limb malformations typically include hypoplasia or aplasia of radial elements including the thumb. Nager syndrome is caused by haploinsufficiency of SF3B4, encoding a spliceosomal protein called SAP49. Here, we report a patient with a loss of function variant in SF3B4 withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A total of 120 articles were screened, among which 24 passed the criteria and were further evaluated 124 (Figure 1). Details of the retrieved studies are shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 120 articles were screened, among which 24 passed the criteria and were further evaluated 124 (Figure 1). Details of the retrieved studies are shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…25 Additionally, a study confirmed that depletion of SF3B4 is not only influenced the neural crest formation but also otic development by modulating the expression of several genes responsible for pan-placodal (eg six1 , dmrta1 , and foxi4.1 ) and otic vesicle development (eg pax8 , tbx2 , otx2 , bmp4 , and wnt3a ). 26 Despite the fact that limb anomalies are considered as a typical characteristic of NS, a broader phenotypic spectrum associated with SF3B4 variants has been identified, as such patient harboring substitution variant (c.1168C > T) displays without any limb defects, 24 implying a phenotypic expansion of SF3B4 variant. Therefore, according to the above reasons, it is possible to speculate that craniofacial, otic, as well as extremities development, may be greatly affected in patients with frameshift variants.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical ES was performed for individuals 1-5 and 8, as previously described. 7,8 Briefly, following short read high throughput sequencing, variants were filtered to 1% minor allele frequency, and then prioritized by genetic and phenotypic assessment. Clinical microarray was performed on individuals 6 and 7 using Cytoscan HD (Affymetrix).…”
Section: Genetic Analysesmentioning
confidence: 99%
“…In humans, pathogenic variants in SF3B4 are responsible for the most common type of acrofacial dysostosis, Nager syndrome 1,2 (OMIM #154400) and Rodriguez syndrome 3 (OMIM#201170), here on referred to as SF3B4-related disorders 4 . Acrofacial Dysostosis and SF3B4-related disorders are characterized by micrognathia and ear defects as well as limb defects.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some patients exhibit rib abnormalities and abnormal vertebral segmentation 1,3 , as well as ventricular septal defect, coarctation of the aorta, hypertrabeculation of the left ventricle and complex structural heart disease 1,5,6 . 41 distinct pathogenic variants have been identified in SF3B4 to date [1][2][3][4][5][6][7][8][9][10][11][12][13][14] , and include whole gene deletion, nonsense, missense, frameshifts, and truncating changes. Since no genotype-phenotype correlation has been found 15 , all mutations are predicted to be nonfunctional.…”
Section: Introductionmentioning
confidence: 99%